2021
DOI: 10.1093/jaoacint/qsab102
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the Cleanliness of Reusable Surgical Instruments in Central Sterile Supply Department by Adenosine Triphosphate Method

Abstract: Background Cleaning is very important in reusable surgical instruments (RSI) reprocessing. Adenosine triphosphate (ATP) method is widely used for cleanliness assessing while few studies focused on using this method on RSIs. Objective To assess the effectiveness of ATP Bioluminescence Assay for monitoring the cleanliness of RSIs. Methods The study conducted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…It is impossible to observe the cleaning effect on the shaft cavity of the robotic arm, the gap at the working end, and other complex structural locations. In recent years, the cleaning efficacy of these devices has been monitored by experts using successively more scientific methods, including ATP detection and residual protein detection, among others ( 11 , 12 ). However, the shaft cavity of the da Vinci system has its own unique lumen structure.…”
Section: Discussionmentioning
confidence: 99%
“…It is impossible to observe the cleaning effect on the shaft cavity of the robotic arm, the gap at the working end, and other complex structural locations. In recent years, the cleaning efficacy of these devices has been monitored by experts using successively more scientific methods, including ATP detection and residual protein detection, among others ( 11 , 12 ). However, the shaft cavity of the da Vinci system has its own unique lumen structure.…”
Section: Discussionmentioning
confidence: 99%
“…If the cleaning is not thorough, any organic matter remaining on the instruments will form a protective film on the surface of microorganisms, affecting the disinfection and sterilization effect, 20 proper cleaning can remove up to 99% of microorganisms, and may extend device life and save medical costs. 12 , 21 Using the proper cleaning method to sanitize surgical instruments and strictly monitor their quality. Therefore, it is suggested that the standardized cleaning process: for special and complicated medical equipment, should be classified by a special person, cleaning separately, reasonable selection of cleaning agent, while the cleaning personnel are required to strictly regulate the operating procedures to prevent cross-infection.…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed that the defect rate of packaging inspection was 1.43 ‰ ~1.67 ‰. 7 Ye et al 12 found that the qualified rate of manual cleaning and mechanical cleaning were 70.59% and 84.97%, respectively. Costa et al 13 still found biofilm and bone fragments by scanning electron microscope after sterilization, which is not surprising given the number of surgical instruments processed.…”
Section: Introductionmentioning
confidence: 99%